Fabrication of a multi-phase porous high-temperature Mo–Si–B alloy by in situ reaction synthesis. (8th August 2019) - Huang, Yongan; Zhang, Laiqi; Wang, Meng; Aindow, Mark
ABSTRACT: The pore formation process has been studied for a high-temperature porous Mo–Si–B alloy produced by in situ reaction synthesis from elemental starting powders. The expansions, phase transformations, microstructure and pore parameters were investigated systematically as a function of the sintering temperature. For sintering temperatures of 1200°C and above, a multiphase mixture of the oxidation-resistant intermetallic compounds Mo3 Si, Mo5 Si3 and Mo5 SiB2 was obtained. It was found that the porous alloys exhibit uniform skeletons with fine grains, high porosities and centred pore size distributions. Characterisation data obtained from samples sintered at temperatures from 1200 to 1600°C are used to deduce the processes which occur at each stage in the reaction synthesis. This helps to explain the formation mechanism for the pores and skeletons in this novel material.